Circulating Irisin, Adropin, and Preptin as Biomarkers of Obesity and Obesity-Related Type 2 Diabetes Mellitus: A Multinomial Logistic Regression and Receiver Operating Characteristic Curve Analysis - Muzaffer Katar; Merve Çatak (Journal of Turkish Clinical Biochemistry, 2026)
Objective: Obesity represents a significant global health concern characterized by substantial metabolic abnormalities and a heightened risk of developing type 2 diabetes mellitus (T2DM). Novel peptides including irisin, adropin, and preptin have been shown to play important roles in the regulation of energy homeostasis and glucose metabolism. However, their relative metabolic associations and combined diagnostic relevance in obesity and obesity-related T2DM remain incompletely understood. Methods: This cross-sectional study included healthy controls, obese individuals, and obese patients with T2DM. Anthropometric measurements and serum levels of irisin, adropin, and preptin were assessed. Group comparisons, correlation analyses, and multinomial logistic regression models were performed to evaluate independent associations after adjustment for potential confounders. Receiver operating characteristic (ROC) curve analyses were performed to evaluate the diagnostic accuracy of individual biomarkers as well as a combined biomarker model. Results: Circulating irisin and adropin levels were significantly lower, whereas preptin levels were significantly higher, in obese and obese+T2DM groups compared with controls. Multivariable-adjusted analyses demonstrated that lower irisin levels were independently associated with obesity and obesity-related T2DM, whereas higher preptin levels were independently associated with obesity-related T2DM. Individual biomarkers exhibited moderate discriminative ability in ROC analyses; however, the combined model incorporating irisin, adropin, and preptin consistently achieved higher area under the curve (AUC) values than individual parameters for both obesity and obesity-related T2DM. Conclusion: Irisin, adropin, and preptin show differential associations with obesity and obesity-related T2DM. The combined assessment of these biomarkers provides improved discriminative performance compared with individual markers and may offer complementary insight into metabolic dysregulation associated with obesity and T2DM.